Características fisiológicas de bactérias diazotróficas isoladas de Brachiaria brizantha cv. Marandu - SILVESTRE, Gilmara Aparecida (2017)
FBN has been intensively studied due to nitrogen (N) supply, thus contributing to the sustainability of agroecosystems, especially in tropical regions, where soils are generally highly weathered and have a low level of natural fertility. The BNF process is carried out by N2-fixing bacteria, which can be found in free life, in association with several plant species or in symbiosis with legumes. Some species of associative bacteria, besides abundantly colonizing the rhizosphere, may also occur endofiticamente, that is, invade the cortex and colonize internal tissues in several plant species and contribute with part of the N necessary to the vegetal development. Therefore, this work was carried out with the objective of analyzing strains of bacteria tolerant to different salt concentrations and the production of the phormonium 3-indole acetic acid. Diversity was observed in relation to tolerance to saline concentrations and in the production of AIA by strains isolated from Brachiaria spp. Or in different grasses. Some of these showed tolerance to high salt concentrations and produced AIA at concentrations that may contribute to plant growth. In the solubilization of reactive natural phosphate in culture medium, it was observed that the contents of P (g L-1) present in the GL medium after The inoculation was superior to the control treatment, except the treatment inoculated with the strain Ab-V5, of the species Azospirillum brasilense the isolates differed among themselves, in the capacity of solubilization of the phosphate.